Experimental Verification of a TH\(z\) Multi-band Metamaterial Absorber - Tran, Van Huynh; Bui, Xuan Khuyen; Vu, Dinh Lam; Bui, Son Tung; Le, Thi Hong Hiep; Nguyen, Thanh Tung (Communications in Physics, 2020)
Multi-band metamaterial absorbers have been of great interest owing to their potentials for a wide range of communicating, sensing, imaging, and energy harvesting applications. In this work, we experimentally investigate a four-band metamaterial absorber operating at THz frequencies. The metamaterials are fabricated using the maskless UV photolithography and e-beam evaporation techniques. The absorption spectra of the proposed absorber are measured using the micro-Fourier transformed infrared spectroscopy. It was demonstrated that multi-band absorption behavior originates from different individual metamaterial resonators. The thickness of the dielectric spacer plays a key role in optimizing the absorption performance, in line with the predicted results on single-band THz absorbers